Different Heat Tolerance of Two Creeping Bentgrass Cultivars Related to Altered Accumulation of Organic Metabolites - Yong Du; Yue Zhao; Zhou Li (Agronomy, 2025)
High-temperature stress is one of the main limiting factors for the cultivation and management of cool-season creeping bentgrass (Agrostis stolonifera). The objectives of the current study were to compare physiological changes in heat-tolerant PROVIDENCE and heat-sensitive PENNEAGLE and further identify differential organic metabolites associated with thermotolerance in leaves. Two cultivars were cultivated under optimal conditions (23/19 °C) and high-temperature stress (38/33 °C) for 15 days. Heat stress significantly reduced leaf relative water content, chlorophyll content, and photochemical efficiency, and also resulted in severe oxidative damage to PROVIDENCE and PENNEAGLE. Heat-tolerant PROVIDENCE exhibited 10% less water deficit, 11% lower chlorophyll loss, and significantly lower oxidative damage as well as better cell membrane stability compared with PENNEAGLE under heat stress. Metabolomic analysis further found that PROVIDENCE accumulated more sugars (fructose, tagatose, lyxose, ribose, and 6-deoxy-D-glucose), amino acids (norleucine, allothreonine, and glycine), and other metabolites (lactic acid, ribitol, arabitol, and arbutin) than PENNEAGLE. These metabolites play positive roles in energy supply, osmotic adjustment, antioxidant, and membrane stability. Heat stress significantly decreased the accumulation of tricarboxylic acid cycle-related organic acids in two cultivars, resulting in a metabolic deficit for energy production. However, both PROVIDENCE and PENNEAGLE significantly up-regulated the accumulation of stigmasterol related to the stability of cell membrane systems under heat stress. The current findings provide a better understanding of differential thermotolerance in cool-season turfgrass species. In addition, the data can also be utilized in breeding programs to improve the heat tolerance of other grass species. However, the current study only focused on physiological and metabolic responses to heat stress between two genotypes. It would be better to utilize molecular techniques in future studies to better understand and validate differential heat tolerance in creeping bentgrass species.